An Italian survey of undeclared allergens in food over the years 2014–2018. Issue 2 (2nd April 2020) - DeCastelli, Lucia; Arioli, Francesco; Bianchi, Daniela Manila; Barbaro, Antonio; Nobile, Maria; Panseri, Sara; Chiesa, Luca Maria
ABSTRACT: Large population studies estimated that the frequency of food allergies is increasing worldwide. In the last two decades, a 'second wave' of the allergy epidemic has emerged as a growing public health problem. EU regulation strengthened information to consumers about allergens in pre-packed food, since December 2014 it has been extended to non-prepacked foods by the Regulation (EU) No 1169/2011 of the European Commission. The present work aims to present a five-year survey on the presence of nine types of allergen in several foods, including food of animal origin and baby food. The concentration found for each irregular allergen is generally low, but some samples with no gluten indication contained a concentration above 10 mg kg −1 with the highest value of 138.5 mg kg −1 in a dietetic food, during the screening in 2017. These data underline the importance and the necessity of a complete food labelling to protect the majority of allergic individuals.